Strategi Pengasuh dalam Mengatasi Kelelahan Belajar (Learning Burnout) Santri di Pondok Muhlihatus Sholihin Pasuruan - Wahyudi Widodo (ALSYS, 2026)
Although learning burnout can reduce santri motivation, concentration, and engagement in learning, studies on caregivers’ strategies for addressing this condition in Islamic boarding school settings remain limited. This study aimed to describe caregivers’ strategies for addressing learning burnout among santri at Pondok Muhlihatus Sholihin Pasuruan. The study employed a qualitative approach with a case study design. The research informants consisted of pesantren caregivers, ustaz, and santri selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation and were subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña, which comprises data collection, data condensation, data display, and conclusion drawing. Data trustworthiness was strengthened through source triangulation, method triangulation, and member checking. The findings showed that caregivers addressed learning burnout through three main strategies, namely identifying symptoms of learning fatigue at an early stage, applying a personal approach accompanied by motivation and the management of santri activities, and strengthening spiritual guidance through congregational prayers, dhikr, Qur’an recitation, and religious lectures. The implementation of these strategies increased learning motivation, improved concentration, restored enthusiasm for participating in learning activities, and created more stable emotional conditions among santri. These findings affirm that caregiving strategies combining psychological, educational, and spiritual approaches play an important role in reducing learning burnout and supporting the creation of a more effective learning process within the Islamic boarding school environment. This study provides practical implications for pesantren administrators in developing caregiving practices that are responsive to the academic, emotional, and spiritual needs of santri.